Applications of artificial intelligence in the AEC industry: a review and future outlook - Huimin Li; Yafei Zhang; Yongchao Cao; Jing Zhao; Zhichao Zhao (Journal of Asian Architecture and Building Engineering)
In the context of “Industry 4.0,” the construction industry is undergoing a continuous process of digital transformation. In recent years, with the rapid development of artificial intelligence (AI) technology, AI has been successfully applied across various domains within the construction sector. This paper conducts a comprehensive review based on scientific bibliometric analysis and systematic evaluation to provide an overview of AI applications and developments in the architecture, engineering, and construction (AEC) industry, as well as to discuss future research trends. Firstly, a bibliometric analysis was carried out on 3,410 journal articles published between 2003 and 2022. This analysis examined characteristics such as annual publication trends, key researchers and their affiliations, countries of origin, collaborative relationships, prominent journals, and keyword clustering. Subsequently, through systematic review, three critical themes in the field were identified and analyzed: performance prediction, intelligent optimization, and engineering safety and risk. To gain a deeper understanding of cutting-edge AI technologies and their potential applications in the AEC sector, potential future research directions were discussed, including digital twins, blockchain, augmented reality, and virtual reality, all aimed at driving the intelligent and digital transformation of the AEC industry.